An investigation of blood transfusion practices in a regional obstetric hospital with no on-site blood bank - Bengesai, Daniel (Department of Obstetrics and Gynaecology, 2024)
Background This study aimed to investigate blood transfusion practices in a regional obstetric hospital with no on-site blood bank. Underpinning this research was the argument that principles of evidence-based medicine should apply to blood transfusions in the same way they do to any other clinical practice area. Considering the limited availability of resources (financial, human and blood products) and the ever-increasing and competing needs facing South Africa, the practices surrounding the use of blood and blood products must be audited. Method This study used a retrospective descriptive audit approach to collect data on blood transfusion management from Mowbray Maternity Hospital, a Regional Hospital in Metro West, Cape Town, which receives complicated obstetric patients from satellite Midwife Obstetric Units (MOUs) and District Hospitals. In addition, an in-depth folder review of two months was also conducted for 118 women to ascertain the precise obstetric indications and decision-making processes. Results During the study period, there were 10030 deliveries, of which 4734 (47, 2%) were caesarean deliveries, 5081(50.7%), were vaginal deliveries, and 215 (2.1%) were assisted deliveries. Only 781women received blood products; thus, the incidence of blood transfusion during this period was 7.8%. Red blood cell concentrate (including emergency red blood cell concentrate) was the most transfused blood product, followed by fresh frozen plasma, cryoprecipitate, and platelets. Approximately 12.6% of the patients received emergency red blood cells, reflecting acute postpartum haemorrhage while cross-matched red blood cell concentrate (RBC), was transfused to 82.2% of the women in the sample. The clinical area was not labelled for 24.1% (n=189) of patients who received blood products. 58% of the blood transfusions were done after hours. Overall, different transfusion patterns were observed for women who received multiple blood products. The in-depth folder review on 118 patients indicated that the leading cause for blood transfusion was postpartum haemorrhage secondary to uterine atony, which accounted for viii 38.1 % of the transfusions. The range of the pretransfusion Hb was 4-9g/dl, with a mean of 6.51(SD±0.07), suggesting that all the women who received blood products were anaemic. Conclusion Overall, the results from this study indicate that the transfusion of blood products was in line with international practice, where RBC is the most transfused product, followed by FFP other products. Regarding the transfusion rate, although it was higher than in most developed countries, it was much lower than in other low-and medium-income countries. However, while a low rate of PPH and blood transfusion rate is preferable, it also indicates thatphysicians have fewer opportunities to train by self-experience. Therefore, the use of protocolsremains central to effective PPH management and the improvement of the quality of care at MMH, and this should be coupled with routine, retrospective audits, as in the case of this study. The specific reasons for blood transfusions also need to be explored in more detail so as to improve patient care accordingly. For instance, the fact that a significant proportion of women who received blood products were diagnosed with anaemia reinforces the need for early detection of and treatment of antepartum anaemia as well as increasing the use of parenteral iron. The results from this study also suggest that data management issues need to be considered, particularly the siloed nature of the data. It is recommended that MMH establish a unified and integrated system for capturing and managing data quality and storage.